Small Group Discussion Learning Method to Increase Student Learning Interest in Fiqh Learning at MI Islamiyah Banjar Rejo - Sodikin, Muhammad; Rohman, Fatkhur (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the application of the Small Group Discussion (SGD) method to improve students' attention and engagement in Fiqh lessons at MI Islamiyah Banjar Rejo. This study involved an experimental group that participated in Small Group Discussion and a control group that participated in traditional lecture-based learning. Data collection was carried out through pretest, posttest, classroom observation, and student surveys to assess the effectiveness of the SGD method in improving student learning outcomes. The results showed a significant increase in the performance of the experimental group, with a higher posttest score compared to the control group. Classroom observations showed that the experimental group showed higher levels of participation, attention, and engagement during the lesson. Survey responses from students in the experimental group showed positive feedback on the SGD method, with students stating that the method made learning more enjoyable and helped them understand Fiqh concepts better. This study concludes that Small Group Discussion can effectively improve students' attention, participation, and academic achievement in Fiqh lessons, and suggests that this method can be useful in other subjects that require critical thinking and collaboration.